Cancer drug resistance is a serious threat in Bangladesh - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier, 2024)
Cancer drug resistance is a serious issue in Bangladesh that must be addressed with effective solutions. The growth of resistant bacterial strains, inappropriate use of antimicrobials, and inadequate healthcare standards in Bangladesh have resulted in a severe problem with cancer medication resistance. A comprehensive strategy will be needed to address these problems, one that includes expanding knowledge of antibiotic resistance, bettering healthcare system regulation, and developing more potent cancer therapies.